DEKONSTRUKSI NARASI GENDER DALAM KITAB FIKIH MADRASAH ALIYAH: PEMBACAAN DERRIDEAN - Muhammad Abdul Aziz (AN-NUR: Jurnal Pendidikan dan Pembelajaran, 2025)
This study aims to deconstruct gender narratives in Islamic jurisprudence (fiqh) textbooks used in Indonesian Islamic senior high schools (madrasah aliyah), utilizing the post-structuralist framework of Jacques Derrida. The research focuses on three core fiqh texts widely referenced in the religious curriculum: Fathul Qarib, Fathul Mu’in, and Kifayatul Akhyar. Employing textual analysis through close reading and Derridean deconstruction, combined with semi-structured interviews with five curriculum authors and analysis of the 2013–2025 national curriculum documents, the study reveals underlying patriarchal biases embedded in the structure of language and classical legal concepts. Findings indicate a problematic binary hierarchy in the portrayal of gender roles, where men are associated with leadership, rationality, and authority, while women are depicted as emotionally unstable, dependent, and confined to domestic spheres. Moreover, the research identifies aporias or internal contradictions in concepts such as qiwamah (male guardianship), nusyuz (disobedience), and wilayatul nikah (marital guardianship), suggesting the possibility of more egalitarian reinterpretations. The study concludes by recommending a revision of religious textbooks to incorporate critical gender perspectives and urges the implementation of teacher training programs in contemporary hermeneutical methods to foster a more equitable and inclusive approach to Islamic education.